(3LGeY GdHjGf Yf JChjd Bi GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3jHOC HChd ShQI GdJhHI , HGdbhd ai JChjd bhdg Ld KfGDg (B"(3HQGAI ef Gddg hQShdg (B" (3bGd CHh LYaQ gPg HQGAI ef Gddg hQShdg aHQGAI eQahYI s
(3BNQgG (B:s
(3BNQ GdehLhO eg (B: (3MOKfi eMeO Hf YeQ Yf eLGgO bhdg gHGA efKhQkG TYGY GdTeS ef GdchI s
(3bWYI efg ai JaSjQ BjGJ eJaQbI ef ShQI GdJhHI GdQYO , Gdcga , GdTYQGA , GdaQbGfs
(3ef JMHjS GdSdWGf CHj YHO Gddg GdefJUQ GdeQjfi HJGQjN (B827 (3g` s
(3fSNI Ydi Qb ZRGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs